Função polinomial do 2º grau : uma sequência didática apoiada nas tecnologias digitais. - Casagrande, Emília (2017)
The research, which forms part of the Information, Communication and Interaction Technologies applied to Science and Mathematics teaching, has as main focus the research on the pertinence of a didactic proposal that involves, besides the rescue of previous knowledge, the use of different Technological resources for the study of the polynomial function of the second degree. This work has as central question: In what way a didactic sequence, supported in different technological resources, contributes to the understanding of the concepts of the polynomial function of the second degree? As a research objective, we sought to develop a didactic sequence that uses different digital resources to study the polynomial function of the second grade, ascertaining its pertinence in terms of favoring students' participation in a more effective learning. In order to meet the above, this dissertation was organized, initially, presenting cognitive theories that support this work, in particular the constructivism of Jean Piaget and constructionism of Seymour Papert. The text then discusses the use of technological resources to support learning, and at the end of the chapter, the contributions of robotics in education are highlighted. This didactic sequence was structured in eight meetings, in which the study of the polynomial function of the second degree was approached using technological apparatuses, software, simulators, among other didactic tools. The didactic proposal was applied in a first year high school class of a public school in the city of Passo Fundo, RS. Finally, data collection had as objective to respond to the initial questioning using four research instruments: analysis of the questionnaires answered by the students, diary of maple filled in by the teacher-researcher, audio of the class recordings and the interviews of the students. These four tools allow us to infer that the use of different technological resources in a Mathematics class can contribute to the learning of this discipline, allowing students to manipulate, interact, visualize, verify, and construct situations that help them in the process of knowledge construction, Making the classes more dynamic, participatory and meaningful. Finally, it is emphasized that this dissertation is accompanied by an educational product, specifically a didactic sequence, in which are found details of the resources used in the meetings and the didactic sequence developed.